Współczesne problemy wartościowania pracy w kontekście elastyczności zatrudnienia - Bodak, Andrzej; Cierniak-Emerych, Anna (Contemporary Problems of Job Evaluation in Context of Flexibility of Employment, 2005)
In traditional meaning job evaluation links oneself mainly with making the measurements of requirements workstation as well as occur rent on him difficulties. Meanwhile, contemporary more often about efficiency of the employees decided their individual features. Trends connected with flexibility of employment assigned the new role of workers, going beyond standard tasks realized on particular workstation. In the article, the main attention was focus on connections between flexibility of employment and tendencies of changes in the field of job evaluation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 13-18